Potential of zeolite and algae in biomass immobilization - Moghaddam, Seyed Amirebrahim Emami; Harun, Razif; Mokhtar, Mohd Noriznan; Zakaria, Rabitah (Hindawi, 2018)
The interest in utilizing algae for wastewater treatment has been increased due to many advantages. Algae-wastewater treatment system offers a cost-efficient and environmentally friendly alternative to conventional treatment processes such as electrocoagulation and flocculation. In this biosystem, algae can assimilate nutrients in the wastewater for their growth and simultaneously capture the carbon dioxide from the atmosphere during photosynthesis resulting in a decrease in the greenhouse gaseousness. Furthermore, the algal biomass obtained from the treatment process could be further converted to produce high value-added products. However, the recovery of free suspended algae from the treated effluent is one of the most important challenges during the treatment process as the current methods such as centrifugation and filtration are faced with the high cost. Immobilization of algae is a suitable approach to overcome the harvesting issue. However, there are some drawbacks with the common immobilization carriers such as alginate and polyacrylamide related to low stability and toxicity, respectively. Hence, it is necessary to apply a new carrier without the mentioned problems. One of the carriers that can be a suitable candidate for the immobilization is zeolite. To date, various types of zeolite have been used for the immobilization of cells of bacteria and yeast. If there is any possibility to apply them for the immobilization of algae, it needs to be considered in further studies. This article reviews cell immobilization technique, biomass immobilization onto zeolites, and algal immobilization with their applications. Furthermore, the potential application of zeolite as an ideal carrier for algal immobilization has been discussed.